Effectiveness of maggot debridement therapy in treating chronic wounds – review of current literature - Gieroń, Monika; Słowik-Rylska, Małgorzata; Kręcisz, Beata (Medical Studies/Studia Medyczne, 2018)
Larval therapy in recent years has gained more interest as a method of treating chronic wounds. It could be an alternative to conventional therapies due to the increasing multidrug resistance of bacteria and observed allergic reactions to antibiotics and disinfectants. The aim of the study was to evaluate the effectiveness and safety of the treatment on the basis of a review of medical databases. Results of the studies have demonstrated greater maggot debridement therapy (MDT) effectiveness in the debridement and stimulation of granulation process over conventional methods. In addition, using this method can shorten the healing time, reduce the consumption of antibiotics, and reduce the cost of treatment. The results of analysed studies are promising; however, it would be advisable to perform randomised, blinded studies with longer follow-up time, in which a larger group of patients would participate.